2015
DOI: 10.1242/dmm.020214
|View full text |Cite
|
Sign up to set email alerts
|

Effects of FSGS-associated mutations on the stability and function of myosin-1 in fission yeast

Abstract: Point mutations in the human MYO1E gene, encoding class I myosin Myo1e, are associated with focal segmental glomerulosclerosis (FSGS), a primary kidney disorder that leads to end-stage kidney disease. In this study, we used a simple model organism, fission yeast Schizosaccharomyces pombe, to test the effects of FSGS-associated mutations on myosin activity. Fission yeast has only one class I myosin, Myo1, which is involved in actin patch assembly at the sites of endocytosis. The amino acid residues mutated in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 55 publications
(91 reference statements)
0
10
0
Order By: Relevance
“…6a-d ). In addition, a point mutation that disrupts motor domain function also prevented myosin localization 45 (Supplementary Fig. 6b , c).…”
Section: Resultsmentioning
confidence: 90%
“…6a-d ). In addition, a point mutation that disrupts motor domain function also prevented myosin localization 45 (Supplementary Fig. 6b , c).…”
Section: Resultsmentioning
confidence: 90%
“…However, we found that the Myo1e tail can successfully substitute for the Myo1 tail to support localization and function of myosin-I at endocytic sites, although contributions of individual tail domains differ between these two myosins. Altogether, this work provides novel insights into the roles of individual protein domains and demonstrates that fission yeast can be used as a model system to study the effects of disease-associated Myo1e mutations located in the tail (21).…”
Section: Introductionmentioning
confidence: 87%
“…On the other hand, performing human-yeast domain switching studies using a model system with a straightforward readout, such as yeast endocytosis, provides a solid foundation for future work aiming to characterize the effects of disease-associated mutations in specific myosin domains. In our previous work, the use of the yeast system for functional testing of the effects of kidney disease-associated HsMyo1e mutations was limited to conserved residues in the motor domain of SpMyo1 (21). By demonstrating that chimeras consisting of SpMyo1 motor and HsMyo1e tail functionally complement myo1Δ while retaining localization requirements similar to those observed for HsMyo1e in mammalian cells, this study expands the utility of S. pombe as a simple model to effectively study disease-associated mutations residing in the HsMyo1e tail.…”
Section: Myosin-i Protein Domain Contributions To Myosin Localizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a point mutation that disrupts motor domain function also prevented myosin localization ( Supplementary Fig. 4g-h; 45 ). Thus, long-tailed myosins (myo1e/f) appear to have a distinctive role at FcR adhesions.…”
Section: Myo1e and Myo1f Localize To Fcr-actin Adhesions During Frustmentioning
confidence: 95%